Control of the Emission of Ammonia through Adsorption in a Fixed Bed of Activated Carbon - C.C. Rodrigues; D. Moraes (Adsorption Science & Technology)
The increase in atmospheric pollution caused by polluting gases has made it necessary to conduct studies aimed at decreasing or treating the emissions of such gases. Due to its increasing presence in the atmosphere, ammonia is one of the most pre-eminent of these. The present work studied the control of the emission of this gas through its adsorption in a fixed bed of activated carbon. The results showed that the adsorption capacity increased from approximately 0.2 to 1.9 mg NH 3 /g carbon as the concentration of ammonia in the gaseous mixture increased (600, 1200, 1800 and 2400 ppm) at the three temperatures employed (40, 80 and 120°C). Increasing the temperature at the concentrations studied caused a decrease in the adsorption capacity, which was affected to a more significant extent by temperature than by the ammonia concentration in the gaseous mixture.